PEMBERIAN ASI EKSKLUSIF DAN PENGETAHUAN IBU DI DESA SUKASARANA KECAMATAN KARANG TENGAH, CIANJUR, JAWA BARAT - Nur Asiah (ARGIPA (Arsip Gizi dan Pangan), 2017)
Awareness of breastfeeding on the wane and are often overlooked by mothers. People are stillworried if given to the baby is not flling so breastfeeding supplemented with formula or water andeven breastfeeding food supplement before 6 months. The purpose of this study was to determinethe exclusive breastfeeding of infants aged 6-12 months and the characteristics and knowledgeof mothers about exclusive breastfeeding in Sukasarana Village, Karang Tengah Subdistrict,Cianjur, West Java. Method used Cross Sectional design. The number of respondents were 235people. Data analysis was done univariat and bivariate using chi square test with alpha <0,05.Mothers who exclusively breastfed (62,2%) more than mothers who did not give exclusivebreastfeeding. Mothers aged < 20 and >35 who gave milk (31,03%), less than the mother who aged 20-35 who gave exclusive breastfeeding to her baby (68,97%). Mothers with high schooleducation and PT who gave breastfeeding (7,59%) less than the mothers who did not educateno school, elementary and junior high school that exclusively breastfed to the baby (92,41%).The percentage of exclusive breastfeeding in mothers who do not work (94,48%)was greatercompared to working mothers (5,52%). Mothers who did not give exclusive breastfeeding tomothers with low knowledge (53,33%) greater than women who are high knowledge (46,67%).Maternal age, maternal education, mother’s job and mother’s knowledge were statisticallyunrelated to exclusive breastfeeding (p> 0.05). However, it is seen that mothers who exclusivelybreastfeed more to high-knowledge mothers. Increased knowledge of exclusive breastfeeding andits benefts is essential to be given to mothers and future mothers. So they have been intent fromthe beginning to give exclusive breastfeeding to their babies.